2022
DOI: 10.1186/s12911-022-01903-9
|View full text |Cite
|
Sign up to set email alerts
|

Which model is superior in predicting ICU survival: artificial intelligence versus conventional approaches

Abstract: Background A disease severity classification system is widely used to predict the survival of patients admitted to the intensive care unit with different diagnoses. In the present study, conventional severity classification systems were compared with artificial intelligence predictive models (Artificial Neural Network and Decision Tree) in terms of the prediction of the survival rate of the patients admitted to the intensive care unit. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The SAPS II includes seventeen variables, and higher total scores are indicative of greater illness severity [ 26 ]. Prior studies have established an association between SAPS II and an elevated mortality rate among ICU patients [ 27 ]. In addition, we discovered a correlation between urine output and mortality in critically ill patients with CHF combined with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The SAPS II includes seventeen variables, and higher total scores are indicative of greater illness severity [ 26 ]. Prior studies have established an association between SAPS II and an elevated mortality rate among ICU patients [ 27 ]. In addition, we discovered a correlation between urine output and mortality in critically ill patients with CHF combined with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The SAPS II score comprises seventeen factors, with higher scores indicating illness severity [ 29 ]. Previous research has shown that SAPS II is related to a greater death rate among ICU patients [ 30 ]. In addition, we discovered that respiratory rate is a significant predictor of death in critically ill patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…39 Studies have also shown the superiority of Machine Learning/AI techniques including DL 25 over conventional statistical analysis for disease detection and prediction of medical outcomes. 40,41 We assessed the importance of the differentially methylated genes on biological pathways, both to further elucidate the molecular mechanisms of PC and also to determine the biological plausibility of our findings. A high percentage of the 66 epigenetically dysregulated molecular pathways identified (Table S3) was related to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…AI techniques are specifically engineered to handle such big data 39 . Studies have also shown the superiority of Machine Learning/AI techniques including DL 25 over conventional statistical analysis for disease detection and prediction of medical outcomes 40,41 …”
Section: Discussionmentioning
confidence: 99%